2015
DOI: 10.1055/s-0035-1555950
|View full text |Cite
|
Sign up to set email alerts
|

Kostensätze zur monetären Bewertung von Versorgungsleistungen bei psychischen Erkrankungen

Abstract: Assessing resource utilisation and costs for treating mental disorders in Germany is difficult. This pertains especially to the numerous non-medical services that are financed by a considerable number of payers. To standardise and simplify cost calculation, we created a database of unit costs for the most important services for mental disorders. We performed a literature and internet search to identify services provided to persons with mental disorders. Unit costs were calculated either by means of public stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…The recorded types of utilized services are priced by using negotiated prices from SHI routine data and aggregated data for staff, material and infrastructure expenses from hospital information and empirical valuation rates according to Grupp et al ( 64 ) for complementary psychiatric services and Krauth et al ( 65 ) for inpatient somatic care, medical rehabilitation and SHI-accredited physicians. The individual data linkage ( Figure 1 ) furthermore enables resource utilization determined via the primary data collection to be validated by corresponding health care utilization determined from SHI claims data.…”
Section: Methodsmentioning
confidence: 99%
“…The recorded types of utilized services are priced by using negotiated prices from SHI routine data and aggregated data for staff, material and infrastructure expenses from hospital information and empirical valuation rates according to Grupp et al ( 64 ) for complementary psychiatric services and Krauth et al ( 65 ) for inpatient somatic care, medical rehabilitation and SHI-accredited physicians. The individual data linkage ( Figure 1 ) furthermore enables resource utilization determined via the primary data collection to be validated by corresponding health care utilization determined from SHI claims data.…”
Section: Methodsmentioning
confidence: 99%
“…Neben diesen Publikationen zum allgemeinen Costing finden sich auch noch Arbeiten zu bestimmten Indikationen (z. B. Kostensätze für psychische Erkrankungen [5]) oder für bestimmte Bevölkerungsteile (z. B. Fragebogen zum Ressourcenverbrauch älterer Menschen [6]), wobei dabei z. T. auf die genannten Standardkostensätze zurückgegriffen wurde.…”
Section: Hintergrundunclassified
“…The CSSRI-EU is a standardized, validated interview to evaluate health care utilization [25,26] and refers to a time period of the last 6 months. Direct costs (in-and outpatient services as well as formal and informal care) were estimated in a second step via monetary valuation with German unit costs [27,28]. Furthermore, medication cost was derived from the German official pharmaceutical index [29].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Furthermore, medication cost was derived from the German official pharmaceutical index [29]. Indirect costs due to absenteeism were estimated by the human capital approach monetarily valuing time absent from work using full-and part-time labor costs for manufacturing and service sectors [28,30]. Measures and procedures beyond the primary outcomes of the study are reported elsewhere [20].…”
Section: Outcome Measuresmentioning
confidence: 99%